The Influence of Pits on the Tribological Behavior of Grey Cast Iron under Dry Sliding. (27th August 2018) - Long, Risheng; Kelly, Peter; Sun, Shaoni; Feng, Jiling; Wang, Xuewen; Li, Wenyue
Abstract : Inspired by the nonsmooth surface of the head of the dung beetle, grey cast iron (GCI) samples with pit textured surfaces were designed and fabricated, based on pin-on-disc friction tester. Using a tribology wear testing rig and APDL programming, the tribological behavior of smooth and textured samples was investigated and reported, both experimentally and numerically. The results show that pits can significantly change the thermal stress and temperature distribution on the surface, which will result in either positive or negative effects on the wear resistance of GCI samples, depending on the parameters. When diameter of the pit (DOP) equals 0.8 mm and distance between pits (DBP) is 1.0 mm, the pit textured surface provided the best wear resistance among all samples tested.